E-government and monitory democracy: Iceland’s crowdsourced constitution - Julie Freeman (2013)
This paper explores government use of information and communication technologies (ICTs) to facilitate civic involvement in democratic reform. It suggests that e-government offers the platforms needed to address increasing external pressures for greater government transparency and responsiveness, and to adapt to changing notions of political representation and participation. This paper draws from Iceland’s constitutional crowdsourcing to illustrate how it encouraged nation-wide public participation in democratic reform through both traditional and online methods. The initiative undertaken in Iceland signals a shift away from the transactional activities often associated with government ICT use, towards more open and responsive egovernment practices that inform democratic decision-making. This paper suggests that, to facilitate civic engagement, such participatory e-government should be an ongoing process that is incorporated into the everyday operations of governments to support and supplement existing political practices.